2023
DOI: 10.1098/rstb.2021.0484
|View full text |Cite
|
Sign up to set email alerts
|

How video calls affect mimicry and trust during interactions

Abstract: Many social species, humans included, mimic emotional expressions, with important consequences for social bonding. Although humans increasingly interact via video calls, little is known about the effect of these online interactions on the mimicry of scratching and yawning, and their linkage with trust. The current study investigated whether mimicry and trust are affected by these new communication media. Using participant-confederate dyads ( n = 27), we tested the mimicry of four behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…Two papers in the special issue provide new insights. Fabiola and colleagues [ 25 ] directly examined how much typical adult participants mimicked the actions of a confederate who was seen face-to-face, on a live video call or in a prerecorded video. Results showed similar mimicry levels between face-to-face and video calls, and both of these resulted in more mimicry than the video condition.…”
Section: Core Processes In Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two papers in the special issue provide new insights. Fabiola and colleagues [ 25 ] directly examined how much typical adult participants mimicked the actions of a confederate who was seen face-to-face, on a live video call or in a prerecorded video. Results showed similar mimicry levels between face-to-face and video calls, and both of these resulted in more mimicry than the video condition.…”
Section: Core Processes In Interactionmentioning
confidence: 99%
“…One common theme across many of these papers is the importance of studying behaviour as participants are engaged in a genuine interaction, not just a tightly controlled task. Several of the studies provide data or reviews (Freeth [32]; Gratch [30]; Kuhlen [33]; Fabiola [25]) which argue that interactional contexts lead to qualitatively different behaviour compared to more traditional non-interactive contexts.…”
Section: Moving Forwardsmentioning
confidence: 99%
“…As a form of participant-confederate dyads technique, this elicitation method allows researchers to explore self-disclosure in dyadic contexts. It includes examining related cognitive, social, affective and cultural mechanisms related to self disclosure in dyadic settings, like reciprocity and self monitoring (e.g., Cheng & Chartrand, 2003;Schloss, Thompson, Gajar, & Schloss, 1985;Sprecher & Treger, 2015), mimicry and imitation (e.g., Cheng & Chartrand, 2003;Diana, Juárez-Mora, Boekel, Hortensius, & Kret, 2023), as well as listening and understanding (e.g., Weger, Castle Bell, Minei, & Robinson, 2014), forming first impressions (e.g., Tucker, Martz, Curtin, & Bazzini, 2007), showing empathy and emotion (e.g., Dichter et al, 2020) and building relationships in long-term experiments. However, the variance between interactions might be a confound in the experimental design.…”
Section: Elicitation Techniquesmentioning
confidence: 99%
“…For instance, mimicry of negative facial expressions (e.g., anger, disgust, fear) has been observed several times to the same extent as affiliative expressions 58,59,63 . Some studies on humans have shown that mimicry of such expressions can result in less liking 58 and decreased trust 64 . Similar findings can be observed in the autonomic domain: mimicry of constricted pupil size -a non-affiliative emotional cue that could signal fatigue, boredom, or social disinterest-can decrease trust 41,65,66 .…”
Section: Mimicry Of Negative Expressions In Human and Non-human Animalsmentioning
confidence: 99%
“…While less extensively studied, the mimicry of scratching and yawning has also been associated with negative outcomes in humans. For instance, the mimicry of yawning resulted in decreased trust in a dyadic setting 64 . Given the evidence for mimicry of negative emotional expressions in humans and non-human animals, we believe that redefining the concept of mimicry according to its presumed evolutionary outcomes (e.g., true mimicry occurs when we mirror positive emotional expressions; otherwise, it's simply a reaction) may erroneously oversimplify the phenomenon.…”
Section: Mimicry Of Negative Expressions In Human and Non-human Animalsmentioning
confidence: 99%